Economic Viability of the Tista River Sand Deposits in Bangladesh An Overview (Journal of Scientific Research, 2017)
The Tista River originates from the Himalaya Mountain, flows through Bangladesh and makes itself as the largest tributary of the Brahmaputra-Jamuna River, having huge sand deposits with valuable minerals. The present work implies economic viability of the Tista River sand deposits measuring heavy mineral concentration and comparing with other established deposits and marking the cut-off grade and prices of these minerals. The study shows that the average content of heavy minerals is 8.26%, containing garnet, ilmenite, magnetite, rutile, zircon and micas. The selected valuable oxides in the form of minerals are SiO2, MgO, K2O and rare earth elements. The commendable amount of SiO2 71.72 wt% makes it feasible as raw material in the glass factory. Another valuable oxide is K2O amounted 2.53 wt% (price per ton in US$ 350-400) makes it praiseworthy. The valuable elements found in deserving quantities are Ba, Rb, Th, V, Cs, Cr, Ni and Co. The remarkable finding of this study is Thorium (Th) measured 28 gm/ton of bulk sand. According to Nobel laureate Carlo Rubbia, thorium (Th) can produce 200 times more electricity than uranium and more environment friendly. So it is economically feasible to take proper initiative to set up mining for sand processing.